Makna Tanda dan Nilai pada Cerita Asal Usul Upacara Penti Masyarakat Wae Mbeleng Desa Benteng Kuwu Kabupaten Manggarai – NTT - Maria Evriana Priska Murni; Hetty Purnamasari; Imron Amrullah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to describe the meaning of signs and values ​​contained in the story of the origin of the Penti ceremony in the Wae Mbeleng community, Benteng Kuwu Village, Manggarai Regency, East Nusa Tenggara. The Penti ceremony is one of the important traditional rituals that contains various symbols and cultural values ​​as a form of gratitude to God and ancestors for the harvest and a request for protection in the coming year. This study uses a qualitative descriptive method with Ferdinand de Saussure's semiotic approach, which dissects signs through the concept of signifier and signified. Data were collected through observation, interviews, and documentation. The results of the study show that the signs in the Penti ceremony, such as symbols of sacrificial animals, mantras, sacred places, and traditional foods, represent the spiritual relationship of the community with God, ancestors, and nature. In addition, values ​​such as ethics, spirituality, kinship, mutual cooperation, as well as educational and social values ​​are reflected in the practice of the ceremony. Thus, the Penti ceremony is not only a form of cultural expression, but also a means of inheriting the noble values ​​of the Manggarai community. This research is expected to contribute to the preservation of local culture and become a reference in the study of cultural anthropology and value education.